Legal Protection For Printing Workers Who Earn Wages Below The Regency Minimum Wage (Case Study In Telang Village, Bangkalan Regency) - Makruf, Makruf; Hariri, Achmad (Universitas Djuanda, 2024)
This research contains harmonious industrial relations between two legal subjects, namely workers and entrepreneurs (employers), which involve the wage system, including work agreements and rights, as well as the obligations of the two legal subjects. In practice, workers often face unfair treatment in employment contracts due to a lack of attention and understanding of the law. Through a Governor's Decree, the provincial minimum wage and district/city minimum wage are determined as wage standards. However, there are still many printing entrepreneurs in Bangkalan Regency who do not meet the UMK requirements in terms of providing wages to workers. This has a negative impact on meeting workers' livelihood needs. It is important to focus on setting fair wages and legal protection for workers. Researchers use empirical legal research methods, which is a research method used to examine the legal bases that apply to actual situations in society. Samples were taken from several strategic printing points including Fix Print, ACC and KOPMA. Even though working time protection is in accordance with the Employment Law, the work agreements entered into by the three printers do not provide other legal protections such as wages, occupational safety and health and worker welfare. Regarding the decision factor to endure below standard wages, it is a personal decision that must be taken by each worker, including economic factors, comfort, security and uncertainty before making a decision.